2007
DOI: 10.1007/bf02912887
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic cardiomyopathy and reactive oxygen species (ROS) related parameters in male and female rats: A comparative study

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 44 publications
(45 reference statements)
1
11
0
Order By: Relevance
“…The formation of ROS from cardiomyocytes is a key factor in the pathogenesis of diabetic complications [43, 48, 49]. In this study, we surprisingly found that high glucose decreased mitochondrial oxidative phosphorylation efficiency, induced mitochondrial swelling, promoted mitochondrial Cyt C release and promoted ROS generation (Fig.…”
Section: Discussionsupporting
confidence: 48%
“…The formation of ROS from cardiomyocytes is a key factor in the pathogenesis of diabetic complications [43, 48, 49]. In this study, we surprisingly found that high glucose decreased mitochondrial oxidative phosphorylation efficiency, induced mitochondrial swelling, promoted mitochondrial Cyt C release and promoted ROS generation (Fig.…”
Section: Discussionsupporting
confidence: 48%
“…In the kidneys of diabetic rats, taurine increased the GSH/GSSG ratio via the reduction of GSSG content, which seems to result from the elevated GR activity without affecting diabetes-induced decrease in renal GSH level. ALX also significantly increased the activity of xanthine oxidase, which is another important biological source of ROS under diabetic conditions (Forbes et al 2008;Akhileshwar et al 2007). Superoxide anions derived from NADPH oxidase contributes to the development of diabetic nephropathy (Toba et al 2009;Onozato et al 2002).…”
Section: Discussionmentioning
confidence: 98%
“…As heart is the major organ subjected to the vascular complications associated with diabetes we selected heart tissue for studying the peroxidation as well as antioxidant level. Akhileshwar et al [20] reported that diabetic state compromise the weak ROS defense systems in the heart thus initiating a lesion at the level of mitochondria which ultimately leads to cardiomyopathy and the effects are especially more pronounced in females. Thus we selected the female rats for our study.…”
Section: Discussionmentioning
confidence: 98%